1972
DOI: 10.1161/01.cir.45.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Evaluation of Left Ventricular Function in Shock Complicating Myocardial Infarction

Abstract: Twenty-two patients with shock complicating myocardial infarction were studied hemodynamically and, despite pharmacologic therapy and regulation of intravascular volume, 16 (73%) subsequently expired. Pulmonary artery end-diastolic pressure (PAEDP) or left ventricular end-diastolic pressure (LVEDP) was > 15 mm Hg in 18 of the 22 patients, and cardiac index (CI) was <2.3 liters/min/m2 in 17 of 22 patients. Fourteen of the 18 patients with PAEDP or LVEDP > 15 mm Hg expired, while two of the four patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…[35][36][37][38][39][40][41][42][43][44][45][46] Most studies have compared hemodynamic values obtained during the first days of the infarct to those obtained at later follow-up. These studies generally have indicated that improvement in cardiac performance may occur gradually in the majority of the surviving patients.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43][44][45][46] Most studies have compared hemodynamic values obtained during the first days of the infarct to those obtained at later follow-up. These studies generally have indicated that improvement in cardiac performance may occur gradually in the majority of the surviving patients.…”
Section: Discussionmentioning
confidence: 99%
“…1). The presence of concomitant low systemic vascular resistance and systemic inflammatory response syndrome with cardiogenic shock is associated with the development of sepsis and poor outcomes [30][31][32] .…”
Section: Pathophysiologymentioning
confidence: 99%
“…For patients with cardiogenic shock owing predominantly to LV failure, right heart catheterization can confirm low cardiac output (cardiac index <2.2 l/min/m 2 ) and high filling pressures (PCWP ≥15 mmHg) 35,32 . For other aetiologies of cardio genic shock complicating AMI, such as ventricular septal rupture, a step-up in oxygen saturation can be seen from the right atrium to ventricle.…”
Section: Diagnosismentioning
confidence: 99%
“…145 In chronic heart failure, cardiac glycosides reduce symptoms and improve clinical status, thereby decreasing the risk of hospitalization for heart failure without effects on survival. 146,147 In AHF, cardiac glycosides produce a small increase in cardiac output 148 and a reduction of filling pressures. 149 In patients with severe heart failure following episodes of acute decompensation, cardiac glycosides have been shown to be efficacious in reducing the re-occurrence of acute decompensation.…”
Section: Class Of Recommendation Iia Level Of Evidence Bmentioning
confidence: 99%